Testament prywatny w orzeczeniach sądów apelacji lwowskiej w okresie międzywojennym - Koredczuk, Józef (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2017)
With respect to inheritance law, in the former Austrian partition during the interbellum, the provisions of the Austrian Civil Code of 1811 ABGB were applicable. According to this Code, only last will statements appointing a heir were considered the last will and testament. Despite the fact that ABGB regulated matters related to inheritance under will relatively exhaustively, certain provisions were interpreted and applied in different ways and constituted basis for court decisions issued in relation to them. A particularly great number of such issues from the interwar period can be found in decisions issued by courts in the region of the Lvov Court of Appeal. Due to the low level of legal culture and for legal safety reasons, ABGB imposed particular formal requirements concerning private wills drawn up out of court.Such a will could be made by hand by the testator a holographic will or by another person an allographic will. It could be delivered in writing or orally, with or without witnesses. The practice of using private wills, widespread among the people of the Lvov Court of Appeal region, was aimed primarily at confirming the prior distribution among the family.
Keywords: ostatnia wola; testament; Sąd Apelacyjny we Lwowie; spadkodawca; świadkowie; testament prywatny